Assessment of Performance of Integrated Solar PV System with Hybrid Energy Storage System - Thakur, HS; Patel, RN (International Journal of Computer Sciences and Engineering, 2025)
It has now been a well-known fact, as a result of extensive research, that energy obtained through solar radiation is intermittent in nature with nearly unpredicted ﬂuctuations in output power. By the virtue of such irregularities, the stability and power quality of Photo Voltaic based power system operation are aﬀected. The present work is aimed to achieve the PV system stability by using battery and ultra-capacitors to support a stand-alone PV power system. Certain loads like induction motor or DC motor draws large current at the time of starting resulting in deep-discharging of the battery as a consequence of which the battery undergoes accelerated aging. Using ultra-capacitors in conjunction with the battery takes care of the sudden initial power demand of the dynamic systems. In the present work a practical approach has been presented to derive the benefit of using ultra-capacitor in conjunction with battery to store energy obtained by solar PV system. Furthermore, the performance of the ultra-capacitor and battery hybrid energy storage scheme is tested and verified by applying different loads on the system. The experimental setup consisted of a 24V, 6.5Ah, lead acid battery bank unit; 3.33F, 24.3V, ultra-capacitor bank unit; a 70W, 32V, PV Panel; dc-dc converter unit; inverter unit, controller unit and load. A comparison has been done between input and output voltages and current waveforms of the inverter with and without ultra-capacitor bank.